ANALYSIS OF THE EFFECTIVENESS OF GOVERNMENT ASSISTANCE FOR MICRO BUSINESS (BPUM) IN THE VILLAGE MANGUNEGARA, MREBET DISTRICT, PURBALINGGA DISTRICT - Miftahul Nurul Huda; Taufik Purboyo; Emilius Gudonohadi (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
This research is entitled